Penerapan Pair Checks Termodifikasi Berbasis Lesson Study untuk Meningkatkan Aktivitas Belajar Mahasiswa pada Mata Kuliah Pengembangan Kurikulum IPA SMP - Nurmala, Rayh Sitta (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
The succsessfull of learning at university is not beyond from lecturer’s role on giving motivation to students to do activity while they do learning activity so that it creates a positive interaction among students as well as between students and lecturer.Learning atmosphere in class on Curriculum Development Course of IPA at Junior High School needs to be improved because their activities in accepting critics and suggestions from their mate was hampered. It was also probability caused by the students in that course came from two different classes. The efforts which can be conducted in improving students’ activity is by applying the Modified Pair Checks Learning Based Lesson Study. The Modified Pair Checks is a modification from Pair Checks learning model, which is modify the number of member in the 1 group from 2 become 4 students, so it is called as Square Checks. The students work together to solve the problems in pair and then they check their assignments with their pairs. Applying the Modified Pair Checks Based Lesson Study aims to improve students’ activity. Subject of the research is the students of Biology Education program on 7th semester offering B and offering C on 2014/2015 academic year in State University of Malang which consists of 17 students, 4 male students and 13 female students. The data analysis used is qualitative descriptive analysis. Result of the research showed that there was an improvement in students learning activity through applying the Modified Pair Checks Based Lesson Study. They were 1,12% in the first meeting and 16,1% in the second meeting.Keywords:        modified pair checks, lesson study, learning activity